Accounting for local temperature effect substantially alters afforestation patterns. (1st February 2022) - Windisch, Michael Gregory; Humpenöder, Florian; Lejeune, Quentin; Schleussner, Carl-Friedrich; Lotze-Campen, Hermann; Popp, Alexander
Abstract: Human intervention in forested ecosystems is hoped to perform a fundamental shift within the next decade by reverting current forest loss—a major source of CO2 emissions—to net forest gain taking up carbon and thus aiding climate change mitigation. The demanded extensive establishment of forests will change the local surface energy fluxes, and with it the local climate, in addition to competing with food and fiber production for land and water. Scenario building models encompass this competition for resources but have turned a blind eye to the biogeophysical (BGP) local surface energy flux disturbance so far. We combine the benefit of CO2 sequestration of afforestation/reforestation (A/R) with the additional incentive or penalty of local BGP induced cooling or warming by translating the local BGP induced temperature change to a CO2 equivalent. We then include this new aspect in the land-use model Model for Agricultural Production and their Impact on the Environment (MAgPIE) via modifying the application of the price on greenhouse gases (GHGs). This enables us to use MAgPIE to produce A/R scenarios that are optimized for both their potential CO2 sequestration and the CO2 equivalent local BGP effect, as well as the socio-economic trade-offs of A/R. Here we show that optimal A/R patterns are substantially altered by taking the local BGP effects into account. Considering local cooling benefits of establishing forests triples (+203.4%) the viable global A/R area in 2100 from 116 to 351 Mha under the conditions of the shared socioeconomic pathway 2 (SSP2) scenario driven by the same GHG price. Three quarters (76.0%, +179 Mha) of the additionally forested area is established in tropical climates alone. Therefore, a further neglect of BGP effects in scenario building models undervalues the benefit of tropical forests while simultaneously running the risk of proposing counterproductive measures at high latitudes. However, the induced focus on tropical forestation intensifies the competition with food production where forests contribute most to mitigation. A/R related trade-offs need to be considered alongside their climate benefit to inhibit unintentional harm of mitigation efforts.